As startups do Sudoeste do Paraná: mapeamento e proposição de instrumentos de avaliação - Ferreira, Elizandro (2021)
Startups are nascent companies constituted by a specific business model, created from innovative ideas and whose purpose is to develop solutions to problems, challenges or market demands. In addition to attracting investments, these companies need to be optimized for their implementation and survival, thus demonstrating the need to strengthen and develop management tools, create and consolidate innovation ecosystems. Given this context, this work aimed to carry out the prospection of startups in the Southwest region of the state of Paraná, as well as contemplate their mapping, diagnosis and the proposal of management instruments. The methodology comprised a bibliometric research for the theoretical basis of the construction of a survey applied to startups in southwestern Paraná. In this sense, it was possible to identify the existence of 128 startups active in the region and to analyze the level of maturity of these companies, questionnaires were applied. As a result, a total of 114 responses were obtained, of which: 57% are in the discovery phase, 11.4% in the validation phase, 16.6% in the operational phase and 15% in the traction phase. However, even within a context of favoring a business ecosystem for technological innovation and support for entrepreneurship (as is the case in the region), most startups analyzed are still in the discovery phase, that is, they are in the initial phase of development of the idea. The results obtained point to the constant need for updating, indicating the importance of continuous research and development in structuring strategies. Bearing in mind that innovation should not only be linked to the construction of startups, but should be integrated and present in all areas of the company, as a management process. This factor is mainly evidenced by the results obtained in the indicators on paying customers, monthly billing and type of investment, also corresponding to the vast majority of respondents who were in the initial phase. In this sense, based on these results, a booklet was created, consisting of contents that enable subsidies for the process of qualified management of startups. In addition, a practical and digital instrument was built that, together with the Booklet, allows an initial diagnosis to be made to indicate the maturity level of the startups, in addition to proposing a cycle of stages covering indicators considered essential for the development of the business. These indicators correspond to market, product, business model, traction and team. In addition, the use of these instruments proposes reflections for planning aimed at business performance. At the end, the tool allows the entrepreneur to dynamically visualize, through a diagnostic graphic, what their main points of attention are, thus basing the development of a performance improvement plan. In conclusion, we will have that innovation must be a continuous and present agenda in all stages and management processes, thus allowing startups to consolidate in a structured way, increasingly approaching satisfactory levels of market performance.